Impact Of Roles Portrayed By Women In Media A Debate On Ethical Or Unethical Content (Trinity Journal of Management, IT & Media (TJMITM), 2014)
The roles which women portray in media have been the subject of much  public criticism and debate. Over the years, this topic has received  serious attention in developing social status of women in the society.  Mass media can be considered as a dynamic instrument to promote  social and economic value for women and foster social development in  urban and also less developed regions of the nation. In order to truly  contribute to the status of women in the society, it is necessary for  researchers and academicians to have a thorough understanding of how  people react or behave after watching the roles essayed by women.  Taking this into consideration, the present study aims to analyze the  “Impact of Roles Portrayed by Women in Media: A Debate on Ethical or  Unethical Content, A study in Gurgaon Region.” This paper reviews &  describes some problem areas whose exploration will provide useful  insights aimed at improving the ethical content in advertising, over-all  marketing strategy and films. The present paper also identifies the  effects of projected roles of women by mass media on women psychology  and health and also on the image of women in the society. Portrayal of  women can have both positive and negative effects on women and their  image. This study will also give an insight on the impact of various  variables such as crime against women, repeated exposure of sexy roles,  reverse gender roles, portrayal of lean, attractive and decorative body  of women etc. on the behavior and psychology of men and women,  especially young girls and boys in the society. The responsibility of  filmmakers, advertisers, marketers, scriptwriters, story writers,  directors and producers, actors etc. becomes imperative in developing  ethical content for the growth of humanity in the world. The focus will be  also on the role of mass media and its impact on public in various  campaigns and court cases such as Femina's Campaign, - “Raising The  Bar”, Jessica Lal Murder, Arushi Murder and Nirbhaya Case. The need  is to enrich the idea of change and development in the society while  developing meaningful and ethical content through mass media.
Keywords: Women portrayal; mass media; ethical content; projected roles